The Effect of Interest in Reading on Mastery of English Vocabulary with Fifth Grade Elementary Students - Herlina Herlina (Studies in English Language and Education, 2016)
The aim of this research is to find out whether there was a positive relationship between students’ interest in reading and their mastery of English vocabulary for fifth grade elementary school students at the lab school in Jakarta. This research used a quantitative method applying a co-relational approach. The population for this research was fifth grade elementary school students from three lab schools. A simple random sampling was used to select a sample of 60 students as respondents from these schools: Lab school Rawamangun in East Jakarta, Lab school Setia Budi in South Jakarta and Lab school Kebayoran also in South Jakarta. Data was collected using a questionnaire with 30 questions requiring answers on a Likert scale and 32 test items were given to each respondent. The conclusion from this research is that there was a positive and significant relationship between interest in reading and mastery of English vocabulary amongst the sample fifth grade elementary school students from these lab schools in Jakarta. Hence, students who had high interest in reading, their mastery of English vocabulary also increased.